(untitled) (UNED Research Journal, 2011)
The advance of urbanization in the Central Valley of Costa Rica is having negative impacts on land use and stresses the environment with a high demand of natural resources, particularly water resources. One example is the Barva Water Table, one of the main water suppliers of semi-urban areas of the Greater Metropolitan Area of Costa Rica, which leads to conflicts between social actors involved with this resource. Comparing land use maps of the area defined by Act LXV of 1888, as well as the literature, we found that forest cover is decreasing while area covered by crops and pastures has increased from 1992 and 2006. At the same time, the forest area has undergone a process of fragmentation, and the increasing number of forest patches has an edge effect in all classes of land use. We recommend sustainable governance of water resources in the protected area’s buffer zone, with the participation of the local government, development associations, and other related public and private institutions.